Psychosocial assessment following self-harm: results from the multi-centre monitoring of self-harm project. - Kapur, N; Murphy, E; Cooper, J; Bergen, H; Hawton, K; Simkin, S; Casey, D; Horrocks, J; Lilley, R; Noble, R; Owens, D (2008)
BACKGROUND: Psychosocial assessment is central to the management of self-harm, but not all individuals receive an assessment following presentation to hospital. Research exploring the factors associated with assessment and non-assessment is sparse. It is unclear how assessment relates to subsequent outcome. METHODS: We identified episodes of self-harm presenting to six hospitals in the UK cities of Oxford, Leeds, and Manchester over an 18-month period (1st March 2000 to 31st August 2001). We used established monitoring systems to investigate: the proportion of episodes resulting in a specialist assessment in each hospital; the factors associated with assessment and non-assessment; the relationship between assessment and repetition of self-harm. RESULTS: A total of 7344 individuals presented with 10,498 episodes of self-harm during the study period. Overall, 60% of episodes resulted in a specialist psychosocial assessment. Factors associated with an increased likelihood of assessment included age over 55 years, current psychiatric treatment, admission to a medical ward, and ingestion of antidepressants. Factors associated with a decreased likelihood of assessment included unemployment, self-cutting, attending outside normal working hours, and self-discharge. We found no overall association between assessment and self-harm repetition, but there were differences between hospitals--assessments were protective in one hospital but associated with an increased risk of repetition in another. LIMITATIONS: Some data may have been more likely to be recorded if episodes resulted in a specialist assessment. This was a non-experimental study and so the findings relating specialist assessment to repetition should be interpreted cautiously. CONCLUSION: Many people who harm themselves, including potentially vulnerable individuals, do not receive an adequate assessment while at hospital. Staff should be aware of the organizational and clinical factors associated with non-assessment. Identifying the active components of psychosocial assessment may help to inform future interventions for self-harm.